2019
DOI: 10.5194/gmd-2019-232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated Monte Carlo-based Quantification and Updating of Geological Uncertainty with Borehole Data (AutoBEL v1.0)

Abstract: Abstract. We provide an automated method for uncertainty quantification and updating of geological models using borehole data for subsurface developments (groundwater, geothermal, oil & gas, and CO2 sequestration, etc.) within a Bayesian framework. Our methodologies are developed with the Bayesian Evidential Learning protocol for uncertainty quantification. Under such framework, newly acquired borehole data directly and jointly update geological models (structure, lithology, petrophysics and fluids), g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…In such a case, classical inversion might still be needed (Scheidt et al, 2018). Recent advances have shown that BEL can also estimate the model parameter distributions and be used as a more traditional inversion technique (Yin et al, 2020;Michel et al, 2020a). However, such more advanced applications require further development of appropriate tools to identify highly non-linear relationships (Park and Caers, 2020) which will inevitably come at a larger computational cost (Michel et al, 2020b).…”
Section: Numerical Methods Development For 4d Data Integration and In...mentioning
confidence: 99%
“…In such a case, classical inversion might still be needed (Scheidt et al, 2018). Recent advances have shown that BEL can also estimate the model parameter distributions and be used as a more traditional inversion technique (Yin et al, 2020;Michel et al, 2020a). However, such more advanced applications require further development of appropriate tools to identify highly non-linear relationships (Park and Caers, 2020) which will inevitably come at a larger computational cost (Michel et al, 2020b).…”
Section: Numerical Methods Development For 4d Data Integration and In...mentioning
confidence: 99%
“…Because the prediction is much simpler than the underlying model, such a small training size is sufficient. Previous BEL applications have shown that this order of magnitude is adequate for making accurate predictions (Athens and Caers, 2019;Hermans et al, 2019Hermans et al, , 2018Hermans et al, , 2016Michel et al, 2020a,b;Park and Caers, 2020;Yin et al, 2020). The influence of the size of the training set is discussed in Section §3.3.2.…”
Section: Whpa Predictionmentioning
confidence: 97%
“…The previously considered hydraulic conductivity fields have two degrees of uncertainty: the mean of hydraulic conductivity and the spatial distribution of the stochastically generated fields. The goal of this chapter is not to demonstrate BEL's capabilities for more complex prior distributions, as this has already been established in previous works such as Hermans et al (2016); Satija and Caers (2015); Yin et al (2020). However, it is important to demonstrate that the experimental design approach remains feasible when the uncertainty is greater.…”
Section: The Case Of Anisotropic K Fieldmentioning
confidence: 99%
See 2 more Smart Citations